1999
DOI: 10.1001/archpedi.153.9.923
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Serial Radiographs in the Management of Pediatric Torus Fractures

Abstract: To assess the utility of radiographs taken immediately after the application of a cast in the management of pediatric torus (or buckle) fractures and to determine the need for serial radiographs taken at follow-up visits. Design: Retrospective medical record review; survey questionnaire of a panel of experts. Setting: The pediatric emergency department (PED) and the pediatric orthopedic clinic at an urban, tertiary care hospital. Patients: All children with torus fractures referred to the pediatric orthopedic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 3 publications
2
39
0
Order By: Relevance
“…The diagnosis is established mainly by the clinical findings and confirmed by plain X-rays [6]. The treatment most commonly offered includes immobilization for a short period of time in plaster-of-Paris, either a backslab or a full cast [3,7].…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis is established mainly by the clinical findings and confirmed by plain X-rays [6]. The treatment most commonly offered includes immobilization for a short period of time in plaster-of-Paris, either a backslab or a full cast [3,7].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, most of the patients who saw a PCP only required 1 visit, and very few had repeat imaging. This finding contrasts with the practice in some orthopedic clinics in which several visits and repeat radiographs seem to be common, 23,24 leading to increased health care costs, loss of patient and provider time, and exposure to potentially unnecessary radiation. 23 Approximately 10% of injuries diagnosed by the ED physician as distal radius buckle fractures were subtle examples of more complex injuries.…”
Section: Figurementioning
confidence: 59%
“…West et al (2005) recommended a future change in treatment policy for torus fractures, when their study found that each of their 39 patients who were randomly assigned to treatment with a cast or soft bandage splint reported no adverse effects, normal fracture healing and had a high degree of patient and parent satisfaction. Farbman et al (1999) retrospectively reviewed medical records over a two year period and assessed the need for follow-up visits in patients with torus fractures. Repeat radiographs were examined, which consequently confirmed no change in bony alignment at any torus fracture site, at any point in time after application of a cast.…”
Section: Resultsmentioning
confidence: 99%
“…Forearm fractures account for approximately 35-45% of all fractures seen in children and of these 85% involve the distal radius (Boyer et al, 2002). Wrist fractures are a common injury amongst children and many of these fractures are diagnosed as a buckle or torus fracture usually occurring in the distal radius (Farbman et al, 1999). Traditionally, treatment requires 2-4 weeks immobilisation in a below elbow short arm cast with orthopaedic follow up, but recent studies have considered looking at the alternative of removable splints.…”
Section: Introductionmentioning
confidence: 99%